Expert Information as an Evidence of Criminal Act of Corruption in Goods and Services Procurement - I Gusti Ayu Stefani Ratna Maharani (University of Udayana, 2018)
This research is focused to identify and analyze the role of the expert information as evidence in the case of corruption. One of the criminal acts of corruption that often occurs in the government is the criminal act of corruption in goods and services procurement, in which the perpetrators have abused the social aid fund from the government. There was the case of criminal act of corruption in goods and services procurement for social aid fund that occurred in Tabanan -Bali, which committed by I Wayan Sukaja, who had corrupted the State’s financial or social aid fund. Within the process of verification in the trial, the public prosecutors submit 2 (two) experts who provided information to assist in terms of verification. This study uses normative research methods. The purpose of this study is to analyze the role of expert information as evidence in criminal act of corruption. The role of an expert cannot be ignored because it will help the judges, prosecutors and lawyers who have limited knowledge. If the expert’s information is contrary, it could be ruled out by the judges but the expert’s information that excluded must be based on clear reason, and the judges must have strong base in assess the role of the expert’s information.